(untitled) - Melik, Rudolf (Hoboken, N.J., 2007)
In The Rise of the Project Workforce, Rudolf Melik reveals how the flattening of the world has fundamentally transformed the structure of modern organizations and the nature of the work we do. He explores the disciplines, technology, and tools required to execute projects and initiatives in today's business climate. Surveying the way we work, collaborate, and make business decisions, Melik shows you how you can manage the constant change and how you can leverage that change and new technologies to beat the competition.
Keywords: Project management,Quản trị dự án